Adsorption/desorption processes dominate the soil P fractions dynamic under long-term N/P addition in a subtropical forest - Cheng Peng; Senhao Wang; Yijing Zhu; Andi Li; Guangcan Yu; Qinggong Mao; Mianhai Zheng; Juan Huang; Xiangping Tan; Jiangming Mo; Wei Zhang (Geoderma)
Despite large phosphorus (P) reserves in subtropical forest soils, P limitation can be exacerbated by elevated atmospheric nitrogen (N) deposition. However, the mechanisms underlying how soil P fraction transformation affects P availability and the key factors that regulate this process under long-term N and/or P addition remain unclear. In this study, in a subtropical forest subjected to 13 years of continuous simulated N and/or P addition, we investigated the response of soil P fractions by modified Hedley P fractionation to long-term fertilization, and how soil geochemical including absorption or desorption with Fe3+, Al3+ and biological processes such as mineralization by phosphatase and assimilation by microorganisms regulate P transformation. We found that N addition significantly increased the Moderately Labile P but did not affect the Labile Pi (inorganic P) and Labile Po (organic P) fractions. These changes were primarily regulated by the promoted geochemical processes, such as Fe3+ (+57.49 %) and Al3+ (+11.20 %) adsorption. However, several soil biological indicators regulating organic and inorganic P transformation, including phosphomonoesterase activity (PME), significantly decreased under long-term N addition. With long-term P addition, Moderately Labile P (contributing to 69 % of the total P increment) was the main destination of the added P, facilitated by the exchange of PO43- with soil organic carbon (SOC) at absorption sites. These findings suggest that soil adsorption/desorption processes dominate the transformation of P fractions in subtropical forests, under both N and P addition. Our findings highlight the importance of P adsorption and desorption processes in highly weathered subtropical forest ecosystems to better understand P transformation mechanisms under global change scenarios.